Enhancing Arabic Vocabulary with Hilyah Book - Mahmudah, Menik (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Mastering Arabic vocabulary remains a significant challenge for non-native learners, particularly those studying in Islamic boarding schools. Traditional vocabulary learning methods, such as rote memorization and isolated word lists, often fail to ensure long-term retention and meaningful application in communication. This study explores the effectiveness of Hilyah Book as a structured vocabulary resource in enhancing Arabic vocabulary acquisition among students at Pondok Pesantren Darullughah Wadda’wah (Dalwa), Pasuruan, Indonesia. Using a qualitative approach, data were collected through semi-structured interviews, classroom observations, and document analysis, involving 25 intermediate-level Arabic learners and 5 Arabic instructors. The findings indicate that Hilyah Book facilitates vocabulary retention through thematic organization, contextualized examples, and bilingual Arabic-English explanations, which help learners establish stronger associations between words and their meanings. Compared to conventional memorization techniques, students reported increased engagement and recall due to the book’s structured format. However, the study also identified challenges, such as difficulties in spontaneous vocabulary application and the need for guided reinforcement through interactive learning activities. These findings suggest that while Hilyah Book is an effective tool for vocabulary acquisition, its impact is maximized when integrated with conversational practice, writing exercises, and teacher-led reinforcement strategies. This study contributes to Arabic language pedagogy by providing empirical insights into the role of structured vocabulary books in enhancing language acquisition in Islamic boarding schools and similar educational settings.